Pengembangan Sistem Informasi Perhotelan menggunakan Metode Rational Unified Process (Studi pada Edotel Pamekasan) - Radea Zulindra Ardisukma; Yusi Tyroni Mursityo; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Edotel Pamekasan is a hotel owned by Public Vocational High School 3 Pamekasan which functions as a hotel as well as a students' learning laboratory. Their operational activities are still done manually, which leads to several problems, such as overlapping room reservations and warehouse's sudden out of stock. Addressing this problem, a solution proposed by improving business processes with the implementation of a hospitality information system. The development of the hospitality information system uses the Rational Unified Process (RUP) method, considering its iterative ability that can respond to requirements change. In the inception phase, business process analysis and improvement focuses on reservations, check-in registration, check-out, warehouse stock management, and operational reporting activities. Continue in the elaboration phase, 7 features, 32 functional requirements, and 1 non-functional requirement are obtained through 2 iterations. In the construction phase, black-box testing showed that the implementation is appropriate, while compatibility testing gave 3 browser recommendations. Last in the transition phase, the system installation was done then User Acceptance Testing to hotel employees gave 93.4% mean score. It can be summed users strongly agreed to the solution proposed. At the end of the research, a hospitality information system was produced in order to manage reservations, guest registration, room search, managing goods management, and operational reporting in Edotel Pamekasan.